Green Synthesis of Zinc Oxide Nanoparticles Using Swertia chirayita for Photocatalytic and Antimicrobial Activity - Khadka, Devendra; Bista, Praveen; Baral, Janaki; Gautam, Surendra Kumar; Bastakoti, Bishnu Prasad; Poudel, Bhoj Raj; Pokhrel, Megh Raj (Journal of Institute of Science and Technology, 2025)
This research work utilized an environmentally friendly and sustainable method to produce zinc oxide nanoparticles (ZnO NPs) using zinc nitrate as a precursor and the leaf extract of Swertia chirayita. The resulting nanoparticles were characterized using various analytical techniques, including UV-vis spectroscopy, X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, field emission scanning electron microscopy (FESEM), and energy-dispersive spectroscopy (EDS). The ZnO nanoparticles were found to have a well-defined crystalline structure, with their average crystallite size measured at around 10.88 nm. Agar well diffusion was used to study the antimicrobial activity, revealing notable antibacterial and antifungal properties, indicating broad-spectrum antimicrobial potential. A degradation efficiency of 95.73 % was achieved for methylene blue (MB) dye by photocatalysis under sunlight within 210 minutes. These findings demonstrate that ZnO NPs synthesized using Swertia chirayita exhibit excellent antimicrobial and photocatalytic properties, making them promising candidates for environmental remediation and biomedicine. This study underscores the potential of green synthesis approaches for developing sustainable nanomaterials.